On willingness to pay and impact mechanism of green agricultural products: a case of shrimp rice in Hunan, China - Zhou, Rongji; Yin, Yuyan (Frontiers in Sustainable Food Systems, 2024)
The burgeoning interest in green agriculture represents a pivotal shift towards environmentally friendly farming systems but sales of its products have been poor. Therefore, guiding consumers to pay reasonably can help green agricultural enterprises formulate appropriate marketing strategies and enhance public health and environmental quality. This paper takes shrimp rice (SR) as an example, based on 1,158 consumers in the largest rice province Hunan, and seeks to detect which factors affect the public’s willingness to pay (WTP) by adopting the Contingent Valuation Method (CVM) and Heckman two-step Model. After removing biased observations, the results show that most respondents recognize the value of SR, whose premium is 1.47 yuan/kg, with a 25.85% premium rate. Moreover, positive external cognitions (psychology, environment, safety, policy) can moderate consumers’ WTP to varying degrees by strengthening their corresponding motivations. In addition, older, highly educated men who are familiar with SR and high-income but small-scale households with children and the elderly are more likely to pay a higher premium. Hence, some recommendations are put forward to enhance consumers’ external cognitions, providing an indispensable scientific basis for developing countries to promote the sustainable development of environmentally friendly agriculture.